A Lytic Lesion on the Head of the Fifth Metatarsal Bone Mimicking Rheumatoid Arthritis in a Geriatric Patient - Metin IŞIK (Archives of Rheumatology, 2012)
Here we present a 75-year-old female patient who presented to our outpatient clinic with arthralgia localized to the metatarsophalangeal (MTP) joints which had lasted for 12 months. On her physical examination, the fifth metatarsophalageal joint was tender and swollen, but there were no signs of any redness or increased warmth. The sedimentation rate (sed rate) was 25 mm/hour, and the level of C-reactive protein (CRP) was 1.4 mg/dL (range 0-0.8). The rheumatoid factor (RF) was 45 IU/ml (range 0-20), and the anti-cyclic citruline peptide (anti-CCP) was 39 U/ml (range 0-25). On the radiological evaluation, an X-ray revealed a lytic lesion on the head of the fifth metatarsal bone. The patient had no inflammatory arthritis; therefore, she was treated as though she had osteoarthritis. After taking paracetamol (4x500 mg/day), she improved. After a more thorough medical inquiry, it was learned that a traumatic fracture of the fifth MTP joint had occurred 13 years previously and that the radiological findings had been accepted as post-traumatic changes. It was now concluded that she had rheumatoid arthritis (RA). Rheumatoid arthritis is an autoimmune, chronic, inflammatory disease of the joints and may lead to MTP joint erosions, periarticular osteopenia, and soft tissue swelling. These erosions first occur and are most frequent at the fifth MTP joint.[<r1>] A history of previous trauma may present confusion in the diagnosis of RA, and it may be difficult to diagnose a geriatric patient with RA since the clinical findings may be insignificant. In addition, nearly 25% of geriatric patients have increased RF and sometimes have slightly increased anti-CCP levels.[<r2>] For these patients, significantly elevated levels of the sed rate, CRP, and, especially, anti-CCP may be very helpful.[<r3>] In conclusion, diagnosis of RA in geriatrics may be prove to be difficult due to RF positivity and insignificant clinical presentation. On the other hand, a radiological exam may also yield confusing and unclear results. Declaration of conflicting interests The authors declared no conflicts of interest with respect to the authorship and/or publication of this article. Funding The authors received no financial support for the research and/or authorship of this article.